DAMPAK HIZIB NAHDLATUL WATHAN TERHADAP INTEGRASI SOSIAL DI DESA PRINGGASELA LOMBOK TIMUR - Muzakki Muzakki; Dewita Hartanti; Muhammad Rifli (Universitas Hamzanwadi, 2021)
This study aims to determine the impact of Nahdlatul Wathan hizib on the social integrity of the people of Pringgasela Village, East Lombok. This research is qualitative research with a case study approach. The results of this study indicate that there has been an increase in social integrity in the Pringgasela community and an increased sense of unity among the Pringgasela community to create a sense of peace and prosperity. This is the impact of the unification of the hizib Nahdlatul Wathan in his community.